Modifikasi Pemberian Tawas Berupa Larutan untuk Penurunan Kekeruhan Air di Desa Sungai Rangas Hambuku - Khair, Abdul; Noraida, Noraida (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
As many as 89.3% of people in Sungai Rangas Hambuku Village still use river water for daily purposes. Turbidity measurements in 2021 amounted to 56 Nephelometric Turbidity Units (NTU) and in 2023 amounted to 53 NTU. This turbidity value has exceeded the maximum level allowed for water for hygiene and sanitation purposes of <3 NTU. Training on how to reduce the level of turbidity using alum has been provided in 2021, but the community has difficulty applying alum in a solid dosage form. The purpose of this activity is to train participants in administering alum to water taken from the river with modifications in the form of a solution preparation. The implementation method is pre-test, provision of training materials and demonstrations, post-test, and follow-up on the application of alum application to reduce water turbidity. Activity location in Sungai Rangas Village The duration of the activity is 6 months. The target number is 50 housewives. The results of the activity showed that participants had increased their knowledge from a score of 41 to 76 to 71 to 100, participants were able to carry out the practice of making a 2% alum solution preparation, participants were able to carry out the practice of reducing the level of water turbidity using alum solution preparation, and participants were able to apply the results of the training in their respective homes.